Batik as a Source of Inspiration for Aesthetic Elements in Efforts to Preserve Traditional Arts and National Identity - Kholis, Achmad Nur (Institut Seni Indoensia Surakarta, 2025)
Culture is a component of life that can be used as a source of inspiration in creating aesthetic elements. Batik as one of the cultural products that has deep details both in terms of meaning and visuals, where it can influence other products. The closeness of the history of batik with the city of Surakarta has a strong correlation and creates new phenomena to other elements. The purpose of this study is to determine the variety of aesthetic elements in the city of Surakarta, and to find out how it can be an effort in preserving traditional arts and national identity. The qualitative descriptive research method was chosen as the basis for the research and supported by observation techniques, interviews, documentation and the addition of literary sources. The results obtained that batik can be a source of inspiration for creating aesthetic elements in various corners and become a representation in the community's approach to preserving culture in the form of traditional arts and strengthening national identity. The smallest level that is attempted can have a wider impact on the environment around the area to the highest level, namely national.